Structural discrimination, denial and the role of intention - Skadegård, Mira C. (Politica, 2023)
Discrimination exists in many forms and in virtually all social contexts. Despite this, the subject continues to evoke discomfort and denial. This is in part due to a shared lack of knowledge and a failure to understand the relevance of the topic for those who do not experience the negative impacts of discrimination. However, movements such as #MeToo and BLM have generated increased curiosity and need for information on the subject. This article addresses structural discrimination, understood as discrimination embedded in structures, norms and common perceptions. Structural discrimination has extensive social consequences and costs. Increased knowledge of (and attention to) structural discrimination and related challenges can therefore contribute to more effective political and social initiatives and strategies that can address discrimination challenges.